One‐pot Catalytic Conversion of Cellulose to Sorbitol and Isosorbide over Bifunctional Ni/TaOPO4 Catalysts. Issue 28 (26th July 2022) - Wu, Yuchen; He, Minyao; Liu, Xuefei; Wang, Xincheng; Song, Yongji; Li, Cuiqing; Liu, Shanshan; Huang, Long
Abstract: Preparation of isosorbide from cellulose by a catalytic one‐pot method under hydrothermal conditions is studied. Phosphate tantalum (TaOPO4 ) was prepared and used as support for the preparation of Ni/TaOPO4 via impregnation of Ni. The catalyst was characterized by X‐ray diffraction, H2 ‐TPR, NH3 ‐TPD, pyridine FTIR and Raman spectroscopy analysis. Results showed that the 5Ni/TaOPO4 (5 % loading of Ni) with a Brønsted/Lewis site (B/L) ratio of 0.153 showed the best catalytic performance and the total yields of sorbitol and isosorbide from cellulose reached 43 % under the conditions of 200 °C and 3 MPa H2 for 24 h. Both Lewis and Brønsted acid sites played crucial roles for the decomposition and dehydration reactions. The synergy of surface acid sites and reduction sites enhanced the cascade dehydration and hydrogenation reactions during the conversion of cellulose to isosorbide. This research is expected to broach a solution for the development of novel solid acid catalysts for the conversion of sugars into platform compounds. Abstract : One‐pot catalytic conversion of cellulose to sorbitol and isosorbide with total yields of 43 % was realized over bifunctional 5Ni/TaOPO4 (5 % loading of Ni) catalysts at 200 °C and 3 MPa H2, resulting from the synergy of surface acid sites and reduction sites.